ANALISIS KESEIMBANGAN AIR DAERAH IRIGASI DOLOK BENDUNG BARANG KAB. DEMAK - Yudaningrum, Farida; Ikhwanudin, Ikhwanudin; Kusmiawati, Siti; Solikhah, Sena Zaimatus (Universitas PGRI Semarang, 2023)
Indonesia as an agricultural country is very interested in the availability of water to support the agricultural sector. One of the efforts to maximize agricultural production results is the utilization of water resources through proper and efficient management of water allocation. D.I Dolok has a large enough land area and of course requires quite a lot of water, so it is necessary to analyze the needs and availability regarding the control of irrigation water for optimal agricultural land. The purpose of this study is to determine the availability of water and the need for irrigation water in D.I Dolok. In this study using Dr. method. FJ. Mock, after we have calculated the data we got from the results of the field survey, the results obtained for the total discharge that can enter the Barang Weir is 51.058 m3/s, and for the amount of water availability in Barang Weir it increases in the rainy season and decreases in the dry season with the largest discharge occurred in January, namely 4,800 m3/sec and the smallest discharge occurred in August, namely 0,160 m3/sec. As for the irrigation water needs of the Barangay Dam, it was obtained 32,967 mÂ³/s with an area of 1296 Ha. Then for the calculation of the water balance by comparing the value of the mainstay discharge with the need for irrigation water with the selected cropping pattern, it can be concluded that the need for irrigation water can be fulfilled from the available mainstay discharge.